2016
DOI: 10.3847/1538-4357/833/2/278
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Interstellar Medium and Cosmic Rays in the MBM 53, 54, and 55 Molecular Clouds and the Pegasus Loop Using Fermi-Lat Gamma-Ray Observations

Abstract: A study of the interstellar medium (ISM) and cosmic rays (CRs) using Fermi Large Area Telescope (LAT) data, in a region encompassing the nearby molecular clouds MBM 53, 54, and 55 and a farinfrared loop-like structure in Pegasus, is reported. By comparing Planck dust thermal emission model with Fermi-LAT γ-ray data, it was found that neither the dust radiance (R) nor the dust opacity at 353 GHz (τ 353 ) were proportional to the total gas column density N (H tot ) primarily because N (H tot )/R and N (H tot )/τ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(51 citation statements)
references
References 45 publications
3
48
0
Order By: Relevance
“…We use the bracketing A eff method to propagate the uncertainty to the spectral parameters. 10 To investigate the largest influence, we replace the A eff with the upper and lower bound of the uncertainty for the sources with spectral indexes freed except the isotropic background and the merged template for weak sources. It results in a 3%−5% change of the emissivity.…”
Section: A Results Of the Baseline Model And The Systematic Uncertaimentioning
confidence: 99%
“…We use the bracketing A eff method to propagate the uncertainty to the spectral parameters. 10 To investigate the largest influence, we replace the A eff with the upper and lower bound of the uncertainty for the sources with spectral indexes freed except the isotropic background and the merged template for weak sources. It results in a 3%−5% change of the emissivity.…”
Section: A Results Of the Baseline Model And The Systematic Uncertaimentioning
confidence: 99%
“…As we saw in Section 2.1 (Figure 1), the correlation between W H i and D em depends on T d , and the temperature dependence is significantly different in the cases of R or τ 353 . Although the model with N H proportional to R is preferred to the one proportional to τ 353 (and the one proportional to W H i ) in terms of ln L by the γ-ray data analysis as described in Section 4.1, the true N H distribution could be appreciably different from either of them; see Section 2.1 for the prerequisites for D em to be proportional to N H and also Mizuno et al (2016), who reported the apparent T d dependence of N H /R and N H /τ 353 in the MBM 53, 54, and 55 clouds and the Pegasus loop.…”
Section: Dust Temperature-sorted Modelingmentioning
confidence: 99%
“…The shaded band shows the systematic uncertainty of our H I emissivity spectrum. (shown in [15], reproduced courtesy of the AAS)…”
Section: Pos(icrc2017)688mentioning
confidence: 99%
“…In the following sections, we describe γ-ray modeling, data analysis, and discussion of the ISM and CR properties in Section 2, 3, and 4, respectively. Readers are also referred to [15] for more details. The Large Area Telescope (LAT) on board the Fermi satellite is a pair-tracking γ-ray telescope, detecting photons from ∼20 MeV to more than 300 GeV [16,17].…”
Section: Introductionmentioning
confidence: 99%